Ultra Vires of the District Court in the Annulment of State Regulations - Arter Lukas Tulia (Indonesian Journal Publisher, 2025)
This study discusses the ultra vires phenomenon carried out by the District Court in canceling state regulations, a legal product of a traditional village in Central Maluku. This study highlights the provisions on the division of absolute and relative authority in the Indonesian judicial system based on Law Number 48 of 2009 concerning Judicial Power, and examines the position of state regulations according to Law Number 12 of 2011 concerning the Formation of Legislation and Law Number 3 of 2024 concerning Villages. By using normative legal research methods through case, statutory, and conceptual approaches, this study finds that state regulations are part of laws and regulations that have binding legal force because they are formed based on the authority and provisions for the formation of laws and regulations. However, the practice of canceling state regulations by the District Court, as in the case examined and tried and decided by the Ambon District Court, is an ultra vires act because the authority to test regulations under the law lies with the Supreme Court. This study emphasizes the need for consistency in the application of judicial authority for the sake of legal certainty and protection of the rights of indigenous peoples.